254 Robotic corpus cancer surgery: ten year mortality data from the UK epicentre in guildford. (4th December 2020) - Uwins, Christina; Tailor, Anil; Chatterjee, Jayanta; Ellis, Patricia; Madhuri, Thumuluru; Michael, Agnieszka; Butler-Manuel, Simon
Abstract : Introduction/Background: The European Society of Gynaecological Oncology(ESGO) and The British Gynaecological Cancer Society(BGCS) recommend laparoscopic surgery for treatment of endometrial cancer. Conversion rates to open can be high when performing surgical staging, particularly in patients with high BMI. The Royal Surrey in Guildford has been performing laparoscopic surgery for endometrial cancer since 2002 and introduced robotic assistance in January 2010. Since then >1400 gynaecological oncology robotic procedures have been performed: the greatest experience in the UK. Objective: Assess surgical outcomes and survival for endometrial cancer since robotic surgery was introduced. Methodology: Retrospective cohort study of surgical treatment for corpus cancer using data collected prospectively on a dedicated database between 1st January 2010 and 31st December 2019. Conversation rate to laparotomy(%), estimated blood loss in ml(EBL), mean and median length of stay(LOS) and 30-day mortality rate(n, %) were calculated. Results: 952 patients received primary surgery for corpus cancer between 2010–2019 Robotic: 734 operations, conversion rate 0.54% Median EBL 50 ml. Median LOS 1 day, 30-day Mortality 1/734(0.14%) Open: 164 operations, Median EBL 500 ml, Median LOS 6 days, 30-day Mortality 5/164(3.05%). In 2019 115/126(91%) of all operations performed for corpus cancer were performed using the Da Vinci Robot with 9 open. Between 2008 and 2019 the median length of stay for patients with corpus cancer fell, from 6 days to 1 day. The rate performed by minimal access surgery(MAS) increased from 33% to 93% despite an increasingly obese population. Conclusion: In 2019, 93% of women treated in Guildford for endometrial cancer, received MAS. Since 2008 our conversion rate to open has fallen from 18% to 1.7%, median EBL from 300 ml to 50 ml and our median LOS from 6 days to 1 night. In our experience, Robotic surgery is extremely well tolerated, safe and predictable. Increasingly, we are performing palliative procedures for women with advanced endometrial cancer with minimal negative impact. Robotic surgery is particularly well suited to high BMI patients; allowing surgical staging to be performed without undue difficulty or surgical compromise. This study demonstrates the lowest 30-day mortality (0.14%) within our robotic cohort. Introduction of the Da Vinci robot in our Centre has led to a revolutionary change in practice with significant patient benefit. Many cases previously thought not fit for surgery at all, are now recommended robotic surgery. Disclosures: Anil Tailor: Proctor for Intuitive Surgical Jayanta Chatterjee: paid-lectures on behalf of pharmaceutical companies Agnieszka Michael: Educational-grants: Clovis, GSK, Ipsen, Novartis, Pfizer, and Tesaro Simon Butler-Manuel: Proctor for Intuitive Surgical, Plasma Surgical & Ethicon